Pharmacy students' knowledge and attitudes regarding cannabis for medical purposes - Stojanović Marina S.; Tomas Ana D.; Paut-Kusturica Milica M.; Rašković Aleksandar L.; Ubavić Milan B.; Tomić Zdenko S.; Sabo Ana J.; Horvat Olga J. (Srpsko lekarsko drustvo, 2017)
Introduction: With the growing trend for legalization of cannabis and its derivatives in Serbia, pharmacists are likely to be consulted on the safety, efficacy, and drug-drug or drug-disease interactions of medical cannabis. Thus, the aim of our study was to assess pharmacy students' knowledge and attitude toward medical cannabis use in Serbia to determine if additional education is needed. Subjects and methods: In the study students from the final year of the study program of integrated academic studies of pharmacy at the Faculty of Medicine, University of Novi Sad were asked to complete an anonymous questionnaire regarding their knowledge and attitudes on the use of cannabis and its derivatives in medical purposes. After giving their written informed consent, they were instructed by the researchers on how to complete the questionnaire. All questionnaires were administered between August 1, 2017 and August 15, 2017. The study was approved by the Ethical Committee of the Faculty of Medicine in Novi Sad; a total of 80 questionnaires were distributed. The questionnaire consisted of 3 groups of statements on which they should mark level of their agreement related to students' knowledge about the use of cannabis and its derivatives in therapeutical purposes, potential negative effects, dispensing in a pharmacy and legalization of cannabis and its derivatives in medical purposes. Results: Although 91.2% of the respondents agreed that cannabis and its derivatives could potentially have therapeutical effects, much lower percentage of respondents (51.3%) were familiar with possible therapeutical effects of cannabis. The same percentage of respondents learned about therapeutical effects of cannabis from sources other than school. About third (31.3%) of our respondents thought that the use of cannabis and its derivatives in therapeutical purposes could cause their abuse and the similar percentage of respondents (33.8%) thought that issuing cannabis and its derivatives in the pharmacy could expose a pharmacist to the certain dangers such as insisting on the issuing without the prescription or robbery. About 90% of the respondents agreed it is necessary to create clear guidelines for the use of cannabis and its derivatives in therapeutical purposes and 76.3% of the respondents thought that doctor's prescription is necessary for their dispensing in a pharmacy. Most of the respondents (75%) agreed that, based on the experiences of the countries which have approved the use of cannabis and its derivatives in therapeutical purposes, its use in those purposes should be approved in Serbia. Conclusion: The majority of pharmacy students supported medical cannabis legalization but only with strict legal regulations and clear guidelines for their use implemented. Further education of the pharmacist about therapeutical effect of cannabis is necessary.